Research on Seismic Test and Calculation Model for Improving Factor of Composite Board with Heat Preservation Function - Shaochun Ma; Hongyuan Fang (Advances in Civil Engineering)
Since the composition and stress state of thermal-insulation composite plates are extremely complex, it is difficult to conduct calculation using conventional methods. Further calculation on its composition structure is even more difficult. To settle this difficulty, this paper conducted experimental investigations on thermal-insulation composite plate and conventional composite plates, and a simplified calculation method with improved factors was deduced based on the experimental results. In this study, the influence of nonstructural thermal insulation system on the composite plate was specially considered. The calculated expressions are deduced, while the stiffness and damping (properties) are determined. Case analysis was carried out to validate the reliability and accuracy of the simplified calculation method of improvement factor. The research results indicate that the modeling difficulty and computational effort are greatly reduced, with relatively small errors. Hence, it is beneficial to the calculation and analysis of composite plates and global structures.